Germinação e mobilização de açucares e proteinas soluveis em sementes de Aspidosperma polyneuron Mull. Arg. submetidas ao estresse hidrico - Rodrigues, Guilherme de Almeida Garcia (2018)
Aspidosperma polyneuron Müll. Arg. is a clímax species, native from Atlantic Forest and characteristic of the Stational Semideciduous Forest that is present in the list of endangered species, being indicated for reforestation of degraded areas. With the aim of producing seedlings in nurseries, this study evaluates the germination behavior and the degradation of total soluble and reducing sugars, sucrose and soluble proteins in Aspidosperma polyneuron seeds under water stress, monitoring the alterations in sugar and protein contents during germination period. The analyzed variables for germination were percentage, mean time, speed index, relative frequency and synchrony, while for degradation were determined the content alterations in quantity of total soluble sugars, reducing sugar, sucrose, albumins, globulins, prolamins and glutelins in the seed intact. The tests were conducted in Petri dishes, using three “Germitest” paper sheets, imbibed with PEG 6000 solutions in different osmotic potentials (-0.2, -0.4, -0.6, -0.8, -1.0, -1.2 e -1.4 MPa) and distilled water to represent the potential of 0.0. Four replicates of 15 seeds were prepared. For degradation analysis, 100 mg fresh mass of each sample was used. The experiment was conducted in completely randomized design, in simple factorial scheme for germination and double factorial scheme (5 collecting periods x 8 osmotic potentials) for degradation. In germination analysis, we verified that as the osmotic potential became more negative, there was a reduction in seed germination percentage, being it null from -0.8 MPa. The germination speed index was also progressively reduced, leading to the increase of germination mean time. While seeds in 0.0 MPa initiated their germination on the seventh day, the seeds exposed to -0.2 took nine days. In - 0.4 and -0.6 MPa, seeds started to germinate in 12 and 14 days, respectively. In degradation analysis, it was observed that soluble proteins were degraded faster in seeds subjected to more negative potentials, while total soluble sugars were degraded slower in lower hydric potentials. Total soluble sugars represent most part of the studied reserves, and glutelin was the most abundant protein in the species seed. A. polyneuron can be considered sensitive to water deficit. Therefore, we recommend that its production by nurseries are conducted under constant water regime, even when high germination uniformity is desired.